2011
DOI: 10.1182/blood-2010-10-314278
|View full text |Cite
|
Sign up to set email alerts
|

IMiD immunomodulatory compounds block C/EBPβ translation through eIF4E down-regulation resulting in inhibition of MM

Abstract: IntroductionImmunomodulatory derivatives of thalidomide (IMiD compounds), such as lenalidomide and pomalidomide, represent a novel class of agents with potent activity against multiple myeloma (MM). 1,2 IMiD compounds were shown to induce antitumor, antiangiogenic, and anti-inflammatory effects. However, the precise mechanisms by which IMiD compounds induce the direct anti-MM effect have not been determined. 3 Escoubet-Lozach et al demonstrated that IMiD compounds induced G 0 -G 1 growth arrest in MM cells bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
71
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(74 citation statements)
references
References 49 publications
0
71
0
3
Order By: Relevance
“…Our data support the notion that Stk40 represses the translation of at least three members of the C/EBP family, including α, β and δ. Translation of C/EBPβ has been shown to be dependent on eIF4E activity, either in an isoform-selective fashion through different translation initiation sites Pause et al, 1994) or in an isoform nonselective manner (Li et al, 2011). Our results suggest that Stk40 controlled translation of C/EBPβ without an isoform preference, as levels of all three C/EBPβ isoforms altered when Stk40 was deleted.…”
Section: Discussionmentioning
confidence: 70%
“…Our data support the notion that Stk40 represses the translation of at least three members of the C/EBP family, including α, β and δ. Translation of C/EBPβ has been shown to be dependent on eIF4E activity, either in an isoform-selective fashion through different translation initiation sites Pause et al, 1994) or in an isoform nonselective manner (Li et al, 2011). Our results suggest that Stk40 controlled translation of C/EBPβ without an isoform preference, as levels of all three C/EBPβ isoforms altered when Stk40 was deleted.…”
Section: Discussionmentioning
confidence: 70%
“…Recent studies demonstrated that high IRF4 levels correlated with increased lenalidomide sensitivity. 17,18 Another study demonstrated that activation of the Wnt/␤-catenin pathway mediates lenalidomide resistance in MM. 15 In a study performed on Del(5q) myelodysplastic syndrome, the secondary resistance to lenalidomide was found to be associated with CDC25C and PP2A overexpression.…”
Section: Discussionmentioning
confidence: 99%
“…23 The following primer pairs were used: human CRBN, forward (59-TCCCGAATGTGTGTTGCCTT-39) and reverse (59-CCAGCGAGGCCATGAAGTTA-39); human PU.1, forward (59-CAAGCTTCGTGGAACTCTCC-39) and reverse (59-ACTGACAATCAGGCGCTTCT-39); and human b-actin, forward (59-CGAGCACAGAGCCTCGCCTTTG-39) and reverse (59-CGACGAGCGCGGCGATATCAT-39). Human IKZF1 mRNA was analyzed via TaqMan real-time RT-PCR (Life Technologies).…”
Section: Real-time Pcr Analysismentioning
confidence: 99%